Clinical evaluation of enhanced recovery versus conventional care in the perioperative period for intradural extramedullary spinal tumors: a study protocol for a multicenter, randomized controlled trial - Jing Chen; Lishuang Chen; Xueqin Hu; Zengna Xing; Yuhui Sun; Fabin Lin; Rui Wang; Chunmei Chen; Yanjuan Lin (Trials, 2024)
Abstract Background This randomized clinical trial protocol aimed to investigate the comparative efficacy of an enhanced recovery after surgery (ERAS) protocol versus traditional perioperative care programs in patients with intradural extramedullary spinal tumors. Methods The study included 180 patients aged 18–80 years, who were randomly assigned to two groups: Group A receiving traditional perioperative care and Group B receiving accelerated rehabilitation perioperative care. The nurse responsible for patient care was informed of the group assignment, but the patients themselves remained blinded to the intervention. The primary outcome measure was the Karnofsky Performance Scale score, which assessed functional status. The secondary outcomes included the Japanese Orthopedic Association Scale, Numeric Pain Rating Scale, length of postoperative hospital stay, duration of urethral catheterization, patient satisfaction questionnaire, and complication rates. Follow-up assessments were conducted telephonically 1 month, 3 months, and 6 months after the surgery. Discussion This study protocol provided a structured approach to assess the potential benefits of ERAS during the perioperative period for patients with intradural extramedullary tumors, aiming to improve patient outcomes and overall care efficiency. Trial registration This study has been registered with the China Clinical Trials Registry (Project No: ChiCTR2200063347). Registered on September 5 2022.